Superalloys 718, 625, 706 and Various Derivatives (2005) 2005
DOI: 10.7449/2005/superalloys_2005_233_242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal-Mechanical Treatment on the Fatigue Crack Propagation Behavior of Newly Developed Allvac 718Plus Alloy

Abstract: The newly developed Allvac 718Plus alloy has shown mechanical properties superior to alloy 718 and comparable to Waspaloy at the temperature up to 704 C. Previous results showed that fatigue crack propagation (FCP) resistance without holding time has no significant difference between three alloys with 718Plus being the best and 718 the lowest. During the holdtime FCP tests, 718Plus shows comparable results to those of Waspaloy and better than Alloy 718. In this paper, the effect of various thermal-mechanical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 8 publications
5
16
2
Order By: Relevance
“…However, contrary to observations in [4,5], performed at 650°C with 100 s hold-time, an improvement in the hold-time FCG properties due to long-time exposure could not be observed in the present case. Here, the exposed material showed similar FCG rates under purely cyclic loading, but during the 90 s hold-time blocks at both 600°C and 700°C the FCG rate increased compared to the as-heat treated material.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, contrary to observations in [4,5], performed at 650°C with 100 s hold-time, an improvement in the hold-time FCG properties due to long-time exposure could not be observed in the present case. Here, the exposed material showed similar FCG rates under purely cyclic loading, but during the 90 s hold-time blocks at both 600°C and 700°C the FCG rate increased compared to the as-heat treated material.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, the exposed material showed similar FCG rates under purely cyclic loading, but during the 90 s hold-time blocks at both 600°C and 700°C the FCG rate increased compared to the as-heat treated material. Liu et al [4,5] reported a reduction in hold-time FCG of roughly one order of magnitude when Allvac 718Plus (in material which had not been subjected to pre-solution soaking) was exposed at 760°C for 350 h.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences between Waspaloy and 718Plus continue in the dwell-FCGR specimens with the W1 dwell fracture surface exhibiting transgranular fracture morphology, although to a lesser extent than in the non-dwell FCGR specimens. These results substantiate what was found in previous studies [5,11].…”
Section: Fcgr and Dwell-fcgr Behavioursupporting
confidence: 94%
“…Alloys 718Plus, 718 and Waspaloy have similar fatigue crack growth rates under 3 seconds triangle loading at 650°C with 718Plus being slightly better. Waspalloy shows the best resistance to fatigue crack growth under hold time fatigue condition while the resistance of 718Plus is better than that of Alloy 718 (Liu et al, 2005).…”
Section: Mechanical Propertiesmentioning
confidence: 99%